MAQÂSHID SYARÎ’AH DALAM FATWA DEWAN HISBAH PERSIS - Huda, Alamul (De Jure: Jurnal Hukum dan Syari'ah, 2014)
This article discuss about Hisbah Council (Dewan Hisbah) as an institution of The Organisation of Islamic Unity  (PERSIS) which has the authority to product fatwa. This research is aimed to elaborate  the concept of  maqâshid syarî’ah used by Hisbah Council in issuing fatwa.  To issue fatwa, they use the methodology (manhaj) and system (thurûq) that has the character and ideology to implements the concept of  back to the al Qur’an and al Sunnah. It means that the fuqaha who engaged in Hisbah Council makes and put of school (madhab)  position "only" as a comparison of legal opinion in all istinbâth process. By his approach they hope  the development of Islamic law (fiqh/ fatwa) can  answer any muslim problems of any where and every time  (sholihun likulli makan wa zaman).